Governance Innovation Through E-Government Platforms: A Study On Service Efficiency And Citizen Satisfaction - Reynilda Reynilda; Aat Ruchiat Nugraha; Umar Sako; Anggalia Wibasuri (UNIVERSITAS PAKUAN, 2025)
This study examines governance innovation through the implementation of e-government platforms, with a particular focus on their influence on service efficiency and citizen satisfaction. As governments worldwide increasingly adopt digital systems to streamline public service delivery, understanding the extent to which these platforms improve administrative performance becomes essential. Using a mixed-methods approach that integrates quantitative service performance indicators and qualitative citizen perception data, this research investigates how digital transformation enhances responsiveness, reduces bureaucratic delays, and facilitates greater transparency in government processes. Findings indicate that e-government platforms significantly contribute to operational efficiency by automating routine tasks, improving interdepartmental coordination, and minimizing service errors. Moreover, increased accessibility, faster service delivery, and user-friendly digital interfaces positively shape citizen satisfaction, strengthening public trust in government institutions. The study further reveals that the success of governance innovation is not solely determined by technological adoption, but also by institutional readiness, digital literacy, and sustained stakeholder engagement. The results underscore the importance of integrating human-centered design and continuous improvement mechanisms to ensure inclusivity and long-term system effectiveness. Overall, this research contributes to the broader discourse on digital governance by providing empirical evidence on how e-government platforms can serve as catalysts for modernizing public administration and enhancing the overall quality of public service experience